The Impact of Smartpm's Ai-Driven Analytics on Predicting and Mitigating Schedule Delays in Complex Infrastructure Projects - Rinkesh Gajera, (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
This study explores the extent to which SmartPM's AI-driven analytics can predict and mitigate the potential impending schedule delays on complex infrastructure projects. From this study, the exhaustive research based on case study and associated data asserts that AI-driven predictive analytics can significantly leverage the outcomes of projects by bringing the identified potential delays to notice before such occurrences and provide actionable insight regarding the possible strategies to mitigate it.
Keywords: Artificial Intelligence; Machine Learning; SmartPM